The Effect of Different Soxhlet Extraction Solvents Towards AntiPropionibacterium acnes Activity of Balik Angin Leaves (Alphitonia incana (Roxb.) Teijsm. & Binn. ex Kurz) : Pengaruh Perbedaan Pelarut Ekstraksi Soxhlet Terhadap Aktivitas AntiPropionibacterium acnes dari Daun Balik Angin (Alphitonia incana (Roxb.) Teijsm. & Binn. ex Kurz) - Ramadhan, Hafiz; Forestryana, Dyera; Subareng, Ahmad Rizal Maulana; Vebruati, Vebruati (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2025)
Background: Acne is a skin infection that may be induced by Propionibacterium acnes. Treatment of acne infection from natural ingredients native to Kalimantan such as Balik Angin or Alphitonia incana (Roxb.) Teijsm. & Binn. ex Kurz can be an alternative therapy. Prior research indicates that leaves macerated with methanol and 70% ethanol solvents can inhibit the growth of P. acnes in the medium category with a Minimum Inhibitory Concentration (MIC) of 3.2%. Objectives: The research purpose is to compare the effect of the different solvents of soxhlet extraction on the antibacterial activity of Balik Angin leaves in inhibiting the growth of P. acnes. Material and Methods: Balik Angin leaves were extracted using the Soxhlet with two different solvents, which were methanol and 70% ethanol, then followed by phytochemical screening. The antibacterial activity assay was carried out by using well diffusion with each sample concentrations of 25.6%; 12.8%; 6.4%; 3.2%; 1.6%; 0.8%; 0.4%; and 0.2%. Results: Both extracts contained the same phytochemical groups, which were phenols, flavonoids, alkaloids, tannins, saponins, and triterpenoids. The antibacterial activity test results showed that both extracts had the same MIC of 0.8%. however, the 70% ethanol extract of Balik Angin leaves was able to provide a larger inhibition diameter average of 9.61±0.35 mm compared to the methanol extract of 9.20±0.22 mm. Nonetheless, there was no significant difference (p>0.05) between both concentrations, when compared to the range of 1.6-25.6%. Conclusions: The conclusion of this research is that differences in Soxhlet extraction solvents in Balik Angin leaves can affect its activity as an anti-Propionibacterium acnes agent.